Visible and near-infrared backscattering spectroscopy for sizing spherical microparticles - Scaffardi, Lucía Beatriz (2007)
Scattering is a useful tool for the determination of particle size in solution. In particular, spectroscopic analysis of backscattering renders the possibility of a simplified experimental setup and direct data processing using Mie theory. We show that a simple technique based on near-infrared (NIR) backscattering spectroscopy together with the development of the corresponding algorithm based on Fourier transform (FT) and Mie theory are a powerful tool for sizing microparticles in the range from 8 to 60 microm diameter. There are three wavelength intervals in the NIR, within which different diameter ranges were analyzed. In each one, the FT yields a coarse diameter value with an uncertainty dependent on the wavelength range. A more accurate value is obtained by further applying cross correlation between experimental and theoretical spectra. This latter step reduces the uncertainty in diameter determination between 30% and 40%, depending on wavelength interval and particle diameter. These results extend previous information on visible backscattering spectroscopy applied to sizing microparticles in the range between 1 and 24 mum diameter. This technique could be the basis for the construction of a portable and practical instrument.